Mathematical investigation of concrete corrosion – a sustainability study - Ondrejka Harbulakova, Vlasta; Estokova, Adriana; Smolakova, Michaela; Kovalcikova, Martina (International Conference “Environmental Engineering”, 2017)
The issue of sustainability is a major spur to innovation in the flied of civil engineering where the important role is decreasing the detrimental effects on environment and save raw materials and energy. Micro silica is a by-product of the industrial manufacture of ferrosilicon and metallic silicon in high temperature electric arc furnaces and is used as an additive for improving concrete properties. The paper presents the results of chemical corrosion and bio-corrosion tests on concrete samples with 5% addition of microsilica as well as on concrete samples with only Portland cement. Chemical corrosion, simulated by sulphuric acid with pH of 4.2, and bio orrosion, simulated by sulphur xidising bacteria Acidithiobacillus thiooxidans, were investigated in terms of basic concrete’s elements leachability. Dissolved amounts of Si and Ca due to both chemical attack and biocorrosion were measured in the period of 3 months. The leaching trends were analysed using a mathematical approach for better interpretation of the results. The correlation analysis confirmed the different leaching trends comparing bio-corrosion and chemical corrosion processes. A high dependency was observed between leaching of Ca and Si from concretes prepared with ordinary cement. In case of concrete sample with microsilica addition no correlation was found out.
Keywords: biocorrosion; chemical corrosion; concrete; correlation; microsilica